Implementasi Kebijakan Pemerintah Dalam Pemberdayaan Masyarakat Towani Tolotang Di Kelurahan Amparita Kabupaten Sidenreng Rappang - Muh Hafizul Hisyam (Departemen Ilmu Pemerintahan Fisip Unhas, 2025)
Community empowerment is one of the essential aspects of improving living standards and promoting socio-economic development in various regions. The Towani Tolotang community possesses significant potential for economic development through community empowerment initiatives, supported by extensive agricultural land and strong local wisdom. However, the implementation of government policies and empowerment programs targeting the Towani Tolotang community remains limited. Therefore, this study aims to examine and analyze the implementation of government policies in empowering the Towani Tolotang community in Amparita Village, Sidenreng Rappang Regency, as well as the factors influencing its implementation. This study employed a qualitative descriptive research method. The research utilized both primary and secondary data sources. Data were collected through observation, interviews, documentation, and literature review. The findings indicate that the implementation of government policies for the empowerment of the Towani Tolotang community in Amparita Village, Sidenreng Rappang Regency, has been carried out through the application of community empowerment principles, namely equality, participation, self-reliance, and sustainability. Overall, the implementation has been relatively successful; however, further improvement is still needed, particularly regarding the sustainability principle in empowering the Towani Tolotang community.